Open Banking API and Employee Competency: Driving Remittance Performance and Customer Growth in Islamic Banking - Arina Al-Haque; Andreas Hadiyono (The Indonesian Institute of Science and Technology Research, 2026)
This paper analyzes the impact of employee competency and business performance on the effectiveness of remittance services, with Open Banking API implementation acting as a supporting technological enabler. The study focuses on an Islamic bank undergoing digital transformation. A quantitative approach was employed using questionnaire data from 40 remittance employees, analyzed through regression methods, and complemented by a before-and-after system performance evaluation based on operational data from 2022 to 2024. The measurement instruments demonstrated excellent reliability (Cronbach’s α > 0.96) and validity (p < 0.05). The statistical results indicate that employee competency has a significant positive effect on remittance business performance. Concurrently, the implementation of the Open Banking API significantly reduced average transaction processing time by 80% (from 10 seconds to 2 seconds), which directly contributed to a 52.9% growth in active partners. Grounded in the Resource Based View (RBV) theory, these findings highlight that orchestrating complex API integrations requires parallel human resource readiness to maximize organizational performance and active partner growth.